The Effect Of Exports And Imports On Employment Opportunities In Indonesia - Sangur, Korneles; Liur, Lisye Magdalena; Tupamahu, Maria Katje (SEAN Institute, 2024)
This research wants to know the partial influence of exports and imports on employment opportunities in Indonesia in the long term and short term. The research method used is the Multiple Regression Error Correction Model (ECM) method. The research results show that in the long term, the import variable is partially declared to reject H0 as evidenced by a probability t-statistic value of <0.05, the export variable is declared to accept H0 as evidenced by a probability t-statistic value of >0.05%. In the short term, the results of the Error Correction Model (ECM) are valid for short term estimation as evidenced by the probability value ECT (-1) <0.05, partially the imported variable is declared to reject H0 as evidenced by the probability t-statistic value <0.05, The eskpro variable is declared to accept H0 as proven by a t-statistic probability value of >0.05%. Policies need to be directed at achieving downstream domestic production and producing finished goods to support the expansion of export markets by increasing the number of export destination countries. And imports need to be directed to support exports and not for consumption.